The Effect of Tax Awareness and Tax Service Satisfaction on Tax Compliance: E-Filing as A Moderating Variable (A Case Study at the Sukoharjo Tax Office) - Fauzan, Dzulfiqar Nur; Ariani, Kurnia Rina (Universitas Syiah Kuala, 2025)
The purpose of this study is to analyze the influence of taxpayer awareness and tax service satisfaction on taxpayer compliance: e-filing as a moderating variable (Case Study at the Sukoharjo Tax Office). This study uses a quantitative approach. The data used are primary data, obtained by distributing questionnaires to taxpayers who are about to fulfill their tax obligations and have used e-filing at the Sukoharjo Tax Office, using a Likert scale. The population in this study is all individual taxpayers registered within the jurisdiction of the Sukoharjo Tax Office. The Slovin formula was used to determine the sample size required for this study. Based on the Slovin formula, the sample size for this study was determined to be 217 respondents. The data analysis method employed in this study was descriptive, utilizing a quantitative approach and Statistical Products and Services Solutions (SPSS) software to determine the significance level of each independent variable coefficient on the dependent variable. The results of this study indicate that Taxpayer Awareness has a significant effect on Taxpayer Compliance. Tax Service Satisfaction does not have a substantial impact on Taxpayer Compliance. E-Filing does not affect Taxpayer Compliance. E-Filing is unable to moderate the relationship between Taxpayer Awareness and Taxpayer Compliance. E-Filing is unable to moderate the relationship between Tax Service Satisfaction and Tax Compliance.